Hiv -Infected Physicians and the Practice of Seriously Invasive Procedures - Gostin, Lawrence (The Hastings Center report, 1989)
The practice of HIV-infected physicians who perform seriously invasive procedures calls for professional guidance to protect patient safety and the privacy of infected physicians.